2008
DOI: 10.3189/002214308784409035
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent thinning of Jakobshavn Isbræ, West Greenland, since the Little Ice Age

Abstract: ABSTRACT. Rapid thinning and velocity increase on major Greenland outlet glaciers during the last two decades may indicate that these glaciers became unstable as a consequence of the Jakobshavn effect (Hughes, 1986), with terminus retreat leading to increased discharge from the interior and consequent further thinning and retreat. To assess whether recent trends deviate from longer-term behavior, we measured glacier surface elevations and terminus positions for Jakobshavn Isbrae, West Greenland, using historic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(137 citation statements)
references
References 37 publications
6
127
0
Order By: Relevance
“…From 1850 to 1964, the calving front shrunk back at a mean speed of 0.3 km/yr but then stagnated from 1964 to 2000. After 2000, it began retreating again at a rate of 3 km/yr (Csatho et al, 2008).…”
Section: First Glaciological Results Using Spirit Dtms and Ortho-mentioning
confidence: 99%
“…From 1850 to 1964, the calving front shrunk back at a mean speed of 0.3 km/yr but then stagnated from 1964 to 2000. After 2000, it began retreating again at a rate of 3 km/yr (Csatho et al, 2008).…”
Section: First Glaciological Results Using Spirit Dtms and Ortho-mentioning
confidence: 99%
“…On the other hand, it also means slowly flowing upstream areas will continue to respond and contribute to mass loss at a reduced rate for the longer-term future as also demonstrated by Price et al (2011) and further, that changes, currently observed upstream, may still be affected by terminus perturbations that happened several decades ago. This is important regarding interpretation of the present observations of thickness change in context of the longer-term terminus retreat of JIB since the Little Ice Age, when the terminus position was 35 km further advanced then at present (Csatho et al 2008;Young et al 2011).…”
Section: Dynamic Adjustmentmentioning
confidence: 99%
“…Khan et al, 2010;Schrama et al, 2011). Whereas the retreat and thinning of numerous marine-terminating glaciers has not been limited to recent years (Csatho et al, 2008), the acceleration of many major outlets and consequent increase in iceberg discharge is, and has become a significant component of the overall net mass loss in the last decade (Rignot and Kanagaratnam, 2006;Howat et al, 2011). However, mass loss is not confined to regions with marine-terminating glaciers.…”
Section: Introductionmentioning
confidence: 99%